Bacteria of Deep-Sea Sediments of the Black Sea Breaking Down Keratin - Avdiyuk, K.V.; Ivanytsia, V.O.; Varbanets, L.D.; Shtenikov, M.D.; Авдіюк, К.В.; Іваниця, В.О.; Варбанець, Л.Д.; Штеніков, М.Д. (PH "Akademperiodyka" of the NAS of Ukraine, 2024)
Down and feather raw materials generated at food processing plants are among the main environmental pollutants. Most enterprises use burial and burning methods to deal with this waste, which negatively affects the environmental situation. The use of enzymatic hydrolysis by decomposer microorganisms is a promising and safe method for processing keratin waste. Earlier, it was shown that bacteria isolated from the bottom sediments of the Black Sea are active producers of elastases, fibrinogenases, and fibrinases. Therefore, the aim of this work was to evaluate the ability of bacteria isolated from the deep-sea sediments of the Black Sea to exhibit other types of proteolytic activity, in particular, to decompose hard-to-reach protein keratin. Меthods. The objects of the study were 20 cultures of bacteria isolated from deep-sea sediments of the Black Sea represented by the genera Bacillus, Metabacillus, Priestia, and Robertmurraya. The cultures were grown under conditions of submerged cultivation at 28 °C, with a nutrient medium stirring rate of 232 rpm for 4 days. For growth, a basic nutrient medium containing 0.5 % defatted chicken feathers as sole sources of carbon and nitrogen was used. The keratinase activity was assessed by UV absorption at 280 nm of hydrolysis products of keratin-containing materials. Protein was determined by the Lowry method, and caseinolytic (total proteolytic) activity was determined by the Anson method. Disulfide reductase activity was measured spectrophotometrically at 412 nm by evaluating the yellow sulfide formed during the reduction of 5,5’-dithiobis-(2-nitrobenzoic acid) (DTNB). Results. It was shown that the cultures of Metabacillus idriensis 2 and Robertmurraya siralis 57, out of twenty studied, did not grow on a nutrient medium with chicken feathers as the only source of carbon and nitrogen. The remaining 18 cultures exhibited varying degrees of keratinase activity (from 3 to 32 U/mL). The highest level of activity is characteristic of the culture Priestia megaterium 035 (32 U/mL). A study of the ability to break down casein showed that the level of total proteolytic (caseinolytic) activity of most cultures ranged from 0.015 U/mL to 0.14 U/mL. The highest total proteolytic activity was demonstrated by Bacillus pumilus A (0.3 U/mL) and Priestia megaterium 55 (0.24 U/mL) cultures, which also demonstrated high keratinase activity. The highest level of disulfide reductase activity was observed in Bacillus pumilus A (63.3 µmol/min), Bacillus subtilis 248 (62.0 µmol/min), and Priestia megaterium 035 (61.3 µmol/min), and the lowest in Bacillus licheniformis 249. Thus, from the deep-sea sediments of the Black Sea, we have isolated a number of active producers of keratinases, representatives of the two genera Bacillus and Priestia, which, after studying their physicochemical and catalytic properties, may turn out to be promising for practical application, in particular in the development of new technologies for the utilization of down and feather poultry farm waste.